Peran LKPD Kreatif Media Canva dalam Meningkatkan Pembelajaran PAI-BP Integratif di Sekolah - Gustia, Nanin; Fadriati, Fadriati (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
This research aims to evaluate the use of innovative Student Worksheets (LKPD) using Canva media in Integrative Islamic Religious Education and Character (PAI-BP) learning in schools and evaluate how this use impacts student encouragement, involvement and understanding. To collect data, this research used observation, interviews and questionnaires. This research uses an action cycle approach, which includes the steps of planning, implementing, observing and reflecting. The research results show that the use of Canva LKPD in Integrative PAI-BP learning increases student motivation, engagement and understanding. Students become more interested, more active, and better understand learning. Teachers also enjoy Canva's LKPD because it allows them to create interesting material that suits students' needs. By using Canva media, teachers can include visual elements to make the material clearer and more interesting. This learning method also encourages students to actively participate in creating LKPD, increasing their understanding and involvement. However, it is important to remember that teachers need adequate training, ongoing technological support, and ongoing evaluation to ensure that creative worksheet materials using Canva media run well. In an era of technology that continues to develop.Keyword : Creative LKPD, Canva Media, Learning Improvement